KEHIDUPAN SOSIAL EKONOMI PEKERJA PEREMPUAN DI PERUSAHAAN TAMBANG PT. WEDA BAY NICKEL (Studi Kasus Masyarakat Lingkar Tambang Desa Lelilef Kecamatan Weda Tengah Kabupaten Halmehara Tengah). - Taslim, Sunaria; Pratiknjo, Maria Heny; Mulianti, Titiek (HOLISTIK, Journal Of Social and Culture, 2020)
The presence of PT Weda Bay Nickel (WBN) Company for The Central Halmahera Site in Tanjung Ulie Lelilef Village, Central Vedic District, has brought hope for the Mining Circle community, especially those in the Ring One category with the hope of absorbing the male and female labor.The opportunity for women to be accepted as mine employees is very welcome in the midst of a business field known to the general public as "the world of Adam". Women are also required to have professionalism and performance equal to men, without abandoning their nature, gentle, conscientious and also assertive. The lure of an established salary is a factor that makes many people want to work in this industry, including women. This does not mean that women are not able and do not want to work in the mines.The emergence of differences in the concept of gender between men and women is due to many things, among which are formed, socialized, strengthened, even constructed socially or culturally, as well as through religious teachings. The prowess of women mining workers can not only be seen in the work area alone. They are generally women who have husbands and children. Such status requires them to be able to double role, as workers as well as housewives. By working as Women Workers, they feel a change in their lives, i.e. they become more cared for by the family, involved in decision making, can help the family economy and improve the social status of the family. Keywords: women workers, gender, Â socioeconomic